Truncated Tau Induces Mitochondrial Transport Failure Through the Impairment of TRAK2 Protein and Bioenergetics Decline in Neuronal Cells - Quintanilla, Rodrigo A.; Tapia-Monsalves, Carola; Vergara, Erick H.; Pérez, María José; Aranguiz, Alejandra (Frontiers in Cellular Neuroscience, 2020)
Mitochondria are highly specialized organelles essential for the synapse, and its impairment contributes to the neurodegeneration in Alzheimer´s disease (AD). Previously, we studied the role of caspase-3-cleaved tau on mitochondrial dysfunction in AD. In neurons, the presence of this AD-relevant tau form induced mitochondrial fragmentation with a concomitant reduction in the expression of Opa1, a mitochondrial fission regulator. More importantly, we showed that caspase-cleaved tau affects mitochondrial transport, decreasing the number of moving mitochondria in the neuronal processes without affecting its velocity rate. However, the molecular mechanisms involved in these events are unknown. We studied the possible role of motor proteins (Kinesin 1 and Dynein) and mitochondrial protein adaptors (RhoT1/T2, Syntaphilin, and TRAK2), in the mitochondrial transport failure induced by caspase-cleaved tau. We expressed GFP, GFP-full-length, and GPF-caspase-3-cleaved tau proteins in rat hippocampal neurons and immortalized cortical neurons (CN 1.4) and analyzed the expression and localization of these proteins involved in mitochondrial transport regulation. We observed that hippocampal neurons expressing caspase-cleaved tau showed a significant accumulation of the mitochondrial population in the soma. These changes were accompanied by evident mitochondrial bioenergetics deficits, including depolarization, oxidative stress, and a significant reduction in ATP production. More critical, caspase-cleaved tau significantly decreased the expression of TRAK2 in immortalized and primary hippocampal neurons without affecting RhoT1/T2 and Syntaphilin levels. Also, when we analyzed the expression of motor proteins: Kinesin 1 (KIF5) and Dynein, we did not detect changes in their expression, localization, and binding to the mitochondria. Interestingly, the expression of truncated tau significantly increases the association of TRAK2 with mitochondria compared with neuronal cells expressing full-length tau. Altogether these results indicate that caspase-cleaved tau may affect mitochondrial transport through the increase of TRAK2-mitochondria binding and reducing ATP production available for the process of these organelles movement. These observations are novel and represent a set of exciting findings where tau pathology could affect mitochondrial distribution in neurons, an event that may contribute to synaptic failure showed in AD.